Production and Transaction Economies and IS Outsourcing: A Study of the U. S. Banking Industry1 - Ang, Soon; Straub, Detmar W. (MIS Quarterly, 1998)
This paper studies economic determinants of IS outsourcing. It argues that a focus on comparative economic theories and models can improve our ability to explain outsourcing within the larger context of organizational strategy and environment. Specifically, the research constructs of production cost, transaction cost, and financial slack are examined simultaneously to understand what influences the outsourcing decision. To empirically test these relationships, information was gathered from senior IT managers in 243 U.S. banks. Financial indices from the archives of the Federal Reserve Bank were a second important source of data. Results of the study show that IS outsourcing in banks was strongly influenced by production cost advantages offered by vendors. Transaction costs played a role in the outsourcing decision, but they were much smaller than production costs. Finally, financial slack was not found to be a significant explanator, although firm size was a significant control factor. The paper has important implications for research and practice. For researchers, the findings provide evidence that financial criteria can be key factors in outsourcing decisions and compare the relative effects of production and transaction costs. For practitioners, the findings suggest that managerial sourcing strategies need to weigh both costs when hiring systems integrators.